The Anthropology of Extraction: Critical Perspectives on the Resource Curse. Issue 2 (1st February 2017) - Gilberthorpe, Emma; Rajak, Dinah
A bstract: Attempts to address the resource curse remain focussed on revenue management, seeking technical solutions to political problems over examinations of relations of power. In this paper, we provide a review of the contribution anthropological research has made over the past decade to understanding the dynamic interplay of social relations, economic interests and struggles over power at stake in the political economy of extraction. In doing so, we show how the constellation of subaltern and elite agency at work within processes of resource extraction is vital in order to confront the complexities, incompatibilities, and inequities in the exploitation of mineral resources.